2014
DOI: 10.1186/1471-244x-14-207
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance, depression and pain in adults with sickle cell disease

Abstract: BackgroundSleep disturbance and depression are commonly encountered in primary care. In sickle cell disease, depression is associated with pain, poor treatment compliance, and lower quality of life. The prevalence of sleep disturbance and its effect upon quality of life in adults with sickle cell disease is unknown. The goal of this study was to determine the prevalence of sleep disturbance and if it is associated with pain and depression in sickle cell disease.MethodsThree hundred twenty eight adults with sic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 32 publications
(42 reference statements)
3
86
0
Order By: Relevance
“…Patients with SCD experience multiple disease-related complications; the physical, psychological, and social effects of these expose these patients to an evaluated risk of acute and chronic fatigue (12), as well as depression, anxiety, stress, and other mental health problems (3,6). This study's findings indicate that fatigue is significantly related to depression, anxiety, and stress; that pain frequency during the study period was significantly related to depression, anxiety, and stress; and that duration of pain was significantly related to depression, anxiety, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with SCD experience multiple disease-related complications; the physical, psychological, and social effects of these expose these patients to an evaluated risk of acute and chronic fatigue (12), as well as depression, anxiety, stress, and other mental health problems (3,6). This study's findings indicate that fatigue is significantly related to depression, anxiety, and stress; that pain frequency during the study period was significantly related to depression, anxiety, and stress; and that duration of pain was significantly related to depression, anxiety, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Dampier et al (13) demonstrated a significant relationship between pain and fatigue in SC patients. Other studies have shown that the prevalence of depression in SC patients is associated with sleep disturbance, poor adherence to treatment, and daily pain (3). Anxiety has been reported as a factor contributing to the frequency and severity of pain in SC patients, as well as reinforcing the pain state and stress; anxiety has also been identified as a precipitating factor in the onset of pain crises (21,22).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations